(untitled) (Journal of Parents and Teachers, 2025)
The article discusses road safety and the importance of educating pedestrians and future drivers about the risks that can arise from not following regulations. To this end, a section is presented that describes the roles of pedestrians, passengers, and drivers. Additionally, the article includes a section on potential problems that can be encountered on the road (traffic, pavement, bridges, etc.).